2017
DOI: 10.1016/j.cbi.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of scalp hair decontamination following exposure to vapours of sulphur mustard simulants 2-chloroethyl ethyl sulphide and methyl salicylate

Abstract: , et al.. Efficacy of scalp hair decontamination following exposure to vapours of sulphur mustard simulants 2-chloroethyl ethyl sulphide and methyl salicylate. Chemico-Biological Interactions, Elsevier, 2017, 267, pp.74-79. 10.1016/j.cbi.2016 Efficacy of scalp hair decontamination following exposure to vapours of sulphur mustard simulants 2-chloroethyl ethyl sulphide and methyl salicylate a b s t r a c tChemical warfare agents are an actual threat and victims' decontamination is a main concern when mass expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…For all interventions, substantial quantities of MeS and BeS remained in the hair following decontamination. This finding is consistent with previous in vitro studies where up to 50% of the tested chemical warfare agent (VX, sulphur mustard) or lipophilic chemical simulant (phorate or MeS) were found to be remaining in the hair following decontamination 16,19,31 . However, it is not consistent with a recent human volunteer field exercise from Chilcott et al 30 that demonstrated high decontamination efficacy for MeS contaminated hair.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For all interventions, substantial quantities of MeS and BeS remained in the hair following decontamination. This finding is consistent with previous in vitro studies where up to 50% of the tested chemical warfare agent (VX, sulphur mustard) or lipophilic chemical simulant (phorate or MeS) were found to be remaining in the hair following decontamination 16,19,31 . However, it is not consistent with a recent human volunteer field exercise from Chilcott et al 30 that demonstrated high decontamination efficacy for MeS contaminated hair.…”
Section: Discussionsupporting
confidence: 92%
“…Outputs of these studies have been informative and have led to changes to both UK and US emergency decontamination protocols for chemical incidents 14,15 . However, few studies have examined the effectiveness of current decontamination interventions in removing chemicals from hair 7,[16][17][18][19][20] and even fewer have done so with human volunteers 10,14,21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Human volunteer trials have demonstrated the effectiveness of such procedures (Chilcott et al , 2019b). Recently, emphasis has been placed on decontamination of scalp hair (Josse et al , 2015; Rolland et al , 2013; Spiandore et al , 2014, 2017, 2018). It is well established that the removal of contaminants from hair is difficult (Duca et al , 2014) and the affinity with which chemicals bind to hair has been exploited for forensic purposes (Blank and Kidwell, 1995).…”
mentioning
confidence: 99%
“…Riviere, Smith, Budsaba, et al, 2001 In vitro study on the efficacy of combined decontamination methods on decontamination efficacy of hair exposed to MeS vapours. Spiandore, Piram, Lacoste, et al, 2016 An in vitro study (using skin mounted on diffusion cells) into the effects of hydrodynamics, detergents and delays on the effectiveness of the ladder pipe decontamination system. Matar, Atkinson, Kansagra, et al, 2014 Human trial…”
Section: Resultsmentioning
confidence: 99%